Prophylactic bracing decreases ankle injuries in collegiate female volleyball players - Pedowitz, D. I.; Reddy, S.; Parekh, S. G.; Huffman, R.; Sennett, B. J. (The American Journal of Sports Medicine, 2008)
Background: Ankle injuries account for the highest percentage of injuries among female collegiate volleyball players. Since 1998, all female volleyball players at the authors` institution have worn bilateral double-upright padded ankle braces at all times.